Я думаю ответ: E)5x2-x-3=0
E) 5x^2-x-3 = 0
D = b^2 - 4ac = (-1)^2 - 4 × 5 × (-3) = 1 + 60 = 61
Пошаговое объяснение:
A) 4x^2-x-1 = 0
D = b^2 - 4ac = (-1)^2 - 4 × 4 × (-1) = 1 + 16 = 17 (Не подходит)
B) 8x^2-x-4 = 0
D = b^2 - 4ac = (-1)^2 - 4 × 8 × (-4) = 1 + 128 = 129 (Не подходит)
C) 8x^2-3x+1 = 0
D = b^2 - 4ac = (-3)^2 - 4 × 8 × 1 = 9 - 32 = - 23 (Не подходит)
D) 2x^2-3x+1 = 0
D = b^2 - 4ac = (-3)^2 - 4 × 2 × 1 = 9 - 8 = 1 (Не подходит)
D = b^2 - 4ac = (-1)^2 - 4 × 5 × (-3) = 1 + 60 = 61 (Подходит)
Я думаю ответ: E)5x2-x-3=0
E) 5x^2-x-3 = 0
D = b^2 - 4ac = (-1)^2 - 4 × 5 × (-3) = 1 + 60 = 61
Пошаговое объяснение:
A) 4x^2-x-1 = 0
D = b^2 - 4ac = (-1)^2 - 4 × 4 × (-1) = 1 + 16 = 17 (Не подходит)
B) 8x^2-x-4 = 0
D = b^2 - 4ac = (-1)^2 - 4 × 8 × (-4) = 1 + 128 = 129 (Не подходит)
C) 8x^2-3x+1 = 0
D = b^2 - 4ac = (-3)^2 - 4 × 8 × 1 = 9 - 32 = - 23 (Не подходит)
D) 2x^2-3x+1 = 0
D = b^2 - 4ac = (-3)^2 - 4 × 2 × 1 = 9 - 8 = 1 (Не подходит)
E) 5x^2-x-3 = 0
D = b^2 - 4ac = (-1)^2 - 4 × 5 × (-3) = 1 + 60 = 61 (Подходит)